EKOLOGI DAN POTENSI POHON NYATOH (Palaquium spp) DI HUTAN SEKUNDERAREAL IUPHHK - HTI PT. BHATARA ALAM LESTARI KABUPATEN MEMPAWAH - Florensius, Marselinus; Herawatiningsih, Ratna; Dewantara, Iswan (Universitas Tanjungpura, 2018)
The forest is a collection of plants dominated by trees with woody vegetation and other vegetation (Arif, 1994). In the absence of replanting or rejuvenation will threaten forest sustainability. The objective of the study was to assess the ecology and potential of nyatoh trees. Provided information on the ecology and potential of nyatoh trees in secondary forest areas. This research was conducted by survey method, the technique of placing the sample was a combination of path and plot line. Each path was placed systematically. The width of the line was 20 m, 750 m long with 7 observation lines. In this path, the measurement of seedling, stake, pole, and tree were done. The result of data analysis in secondary forestwere 46 tree species at all growth level, from 46 species of tree there were 2 species of nyatoh tree ie nyatoh klincir (Palaquium rostratum) and nyatoh sangai (Palaquium obtusifolium). The dominant plant species for seedlings, stakes, poles and trees were wood with the value of INP respectively 16,18%, 24,74%, 25,26% and 28,26%. Types strongly associated with nyatoh include Mentibu (Dactylocladus stenostachys Oliv) with Ochiai index 0.51, followed by Change (Eugenia sp) with index of 0.49, Tekam (Hopea dasyphyla V.SI) with index of 0.49.Keywords: Palaquium spp, Nyatoh Ecology, Nyatoh Potential, Secondary Forest